Does Empathy Attenuate the Criminogenic Effect of Low Self-Control in Late Life? - Hirtenlehner, Helmut (International journal of comparative and applied criminal justice, 2023)
The present study investigates whether empathy shapes the criminogenic effect of low self-control in late adulthood. Based on the assumption that the capacity to understand and share the thoughts and emotions of other people moderates the significance of the capability to consider the distant consequences of behaviour on oneself, we posit that poor self-control is less consequential among senior citizens of high empathy. The results of a postal survey of 3,000 randomly selected older adults from Germany indicate that both low trait self-control and weak trait empathy increase offending in advanced age. Furthermore, the findings provide evidence of an interaction according to which the relationship between the risk-taking component of the self-control trait and criminal activity is stronger for older adults characterised by low empathy. Impulsivity, on the other hand, seems to mediate the association of empathy and offending in late life.